2001
DOI: 10.1002/gene.1020
|View full text |Cite
|
Sign up to set email alerts
|

The winged helix/forkhead transcription factor Foxq1 regulates differentiation of hair in satin mice

Abstract: Satin (sa) homozygous mice have a silky coat with high sheen arising from structurally abnormal medulla cells and defects in differentiation of the hair shaft. We demonstrate that the winged helix/forkhead transcription factor, Foxq1 (Forkhead box, subclass q, member 1) is mutant in sa mice. An intragenic deletion was identified in the radiation-induced satin mutant of the SB/Le inbred strain; a second allele, identified by an N-ethyl-N-nitrosourea (ENU) mutagenesis screen, has a missense mutation in the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 28 publications
3
93
1
2
Order By: Relevance
“…40 Mice homozygous for a Foxf2 knockout allele exhibited cleft of the secondary palate and died within 12-18 h of birth with other defects secondary to the cleft and no other skeletal anomalies; 42 a recent study of a Foxf2 missense mutation suggested that the Foxf2 gene also has a role in anterior segment ocular development in mice, whereas palatal defects were not observed. 43 Although no skeletal defects were reported in Foxq1 deficient mice, 44 one recent study detected Foxq1 expression in the developing craniofacial cartilage in zebrafish. 45 Further studies of patients with terminal and interstitial deletions will help to define which genes are critical for different aspects of 6p25 deletion phenotypes.…”
Section: Foxc1 Mutations: Phenotypes and Genotypesmentioning
confidence: 99%
“…40 Mice homozygous for a Foxf2 knockout allele exhibited cleft of the secondary palate and died within 12-18 h of birth with other defects secondary to the cleft and no other skeletal anomalies; 42 a recent study of a Foxf2 missense mutation suggested that the Foxf2 gene also has a role in anterior segment ocular development in mice, whereas palatal defects were not observed. 43 Although no skeletal defects were reported in Foxq1 deficient mice, 44 one recent study detected Foxq1 expression in the developing craniofacial cartilage in zebrafish. 45 Further studies of patients with terminal and interstitial deletions will help to define which genes are critical for different aspects of 6p25 deletion phenotypes.…”
Section: Foxc1 Mutations: Phenotypes and Genotypesmentioning
confidence: 99%
“…FOXQ1 (also known as hepatic nuclear factor-3 homolog-1, HFH1), a member of the FOXQ subfamily, is expressed in multiple tissues, including kidney, stomach, liver, bladder and other tissues [16][17][18]. FOXQ1 has a role in hair follicle development and FOXQ1 mutant mice have a silky shiny coat appearance [17].…”
Section: Introductionmentioning
confidence: 99%
“…FOXQ1 has a role in hair follicle development and FOXQ1 mutant mice have a silky shiny coat appearance [17]. Mice with FOXQ1 deficiency exhibit a lack of gastric acid secretion [19].…”
Section: Introductionmentioning
confidence: 99%
“…FoxQ1 transcripts have been identified from the adult tissues of humans, mouse, and rat, showing the kidney and gut to be sites of expression (Clevidence et al, 1993;Frank and Zoll, 1998;Bieller et al, 2001). A Foxq1 mutation has been linked with the satin strain of mouse, named for its silky coat, and subsequently Foxq1 was found expressed in hair follicles (Hong et al, 2001). Vertebrate embryonic expression has been studied in X. tropicalis, and is seen in the pharyngeal pouches, tongue, part of the stomach, and the first section of the outer coil of the intestine (Choi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%